Checklist of nematode parasites of amphibians from Argentina - González, Cynthya Elizabeth; Inés, Hamann Monika (Zootaxa, 2015)
This review includes information about 47 taxa of nematode parasites reported from 34 species of Argentinean amphibians, all belonging to order Anura (33 native species and 1 introduced species). Thirty four nematode species have been reported as adults and 13 species were reported as larvae (10 taxa) or juveniles (3 taxa). Two species, Cosmocerca parva and C. podicipinus (Cosmocercidae), collected as adults, are the most commonly occurring adult nematodes in Argentinean amphibians; each of them parasitize 14 amphibian species. The bufonid Rhinella schneideri and the leptodactylid Leptodactylus bufonius present the highest species richness of parasitic nematodes (9 species); followed by Rhinella fernandezae, R. arenarum and Leptodactylus chaquensis, each of which is parasitized by 8 nematode species. Mean species richenss was highest for the family Bufonidae (4.5±3.4; range: 1-9); followed by the Leptodactylidae (3.5±2.8; range: 1-9). Data on hosts, geographical distribution, site of infection, location of deposited materials, and information about life cycles are provided. This is the first compilation of information on nematode parasites of amphibians in Argentina.